Morphological Traits, Phenological Development and Water Productivity of Yaghouti Grapevine Under Stage‐Specific Deficit Irrigation in a Hyperarid Environment - M. Fazeli Rostampour (Irrigation and Drainage, 2026)
Efficient irrigation management is essential for sustainable viticulture in hyperarid regions. This 3‐year study (2022–2024) in south‐eastern Iran employed a strip–split plot design to evaluate three irrigation regimes—full irrigation, moderate deficit (50% soil moisture depletion) and severe deficit (70% depletion)—across four critical phenological stages. Climatic variability, ranging from a mild 2023 season to extreme thermal shocks in 2024, significantly influenced absolute physiological traits. Despite these interannual fluctuations, irrigation regimes consistently modulated leaf architecture and water productivity (WP). Specifically, deficit irrigation applied between veraison and harvest enhanced WP by 19%–44% (moderate) and 11%–20% (severe) compared with full irrigation. These gains were closely coupled with adaptive morphological plasticity; moderate stress induced strategic reductions in leaf area index and specific leaf area, effectively minimising canopy transpiration without compromising yield. The findings further revealed that supraoptimal temperatures (> 40°C) necessitated these physiological adjustments, whereas severe water stress during early spring thermal peaks or late‐winter cold shocks induced detrimental declines in leaf development. Overall, targeted moderate deficit irrigation during late‐season stages represents a robust strategy for enhancing WP while maintaining canopy integrity under volatile climatic conditions.